EVALUATION OF LIGHTING FOR VISUAL PERFORMANCE IN PPAG OFFICE BUILDING PARAHYANGAN CATHOLIC UNIVERSITY, BANDUNG - Saraswati (Jurnal Riset Arsitektur, 2019)
Abstract- Lighting (daylight and artificial) for office is meant for work performance and comfort. The main purpose is to make the task easily identified. Illumination level and glare are indicators for visual performance. PPAG office at Parahyangan Catholic University is now used to accommodate administrative activities by technic faculty’s staffs. PPAG office has some physical conditions that affecting its visual performance. Room and furniture layout, light source position and transparent façade affect the illuminance level on the task, and may cause direct and indirect glare from the sun and lamp.This evaluative research is using comparative method, by comparing on-site data with literatures; and explorative-descriptive to analyze data: exploring impact and causes that being explained descriptively. Illumination level measurement was done digitally using dialux evo to get a precise and quicker result, and sun glare possibilities are assessed by studying the horizontal sun shading effectiveness.Research concludes that visual performance in PPAG office is less than optimal, where 77,9% illumination level at its visual task are measured to be less than its standard, some sun glare at east and west zones, and indirect glare from reflected light on the desk in cubicle room. Therefore it could be optimalized by correcting the furniture layout, rezoning, and adding some shading elements. Key Words: lighting, visual performance, PPAG office at Unpar